Stevens–Johnson syndrome/toxic epidermal necrolysis overlap syndrome due to oral cefuroxime - D Prabath Kumar; G Niveditha; B Siddhartha Kumar; J Indirakshi; Pilla S.Surya Durga Devi; Alladi Mohan (Journal of Clinical and Scientific Research, 2019)
Stevens–Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are life-threatening and severe cutaneous adverse drug reactions characterised by epidermal detachment presenting as blisters and differ only by their extent of skin detachment. A 22-year-old male presented to our tertiary care teaching institute with fever for the preceding 5 days and macular rash over the back for the past 1 day. Before this, he had consulted a local physician for fever and was using oral cefuroxime (250 mg bid) for the past 5 days. General physical examination revealed fever (103oF), conjunctival congestion, generalised maculopapular rash and ulcers over the lips. He was admitted to medical intensive care unit. On the next day, fever persisted; rash had worsened, conjunctivitis developed and skin peeling became evident, involving >10% but <30% of body surface area. At this point in time, a diagnostic possibility of an adverse drug reaction was considered and the patient's history was thoroughly reviewed again. Oral cefuroxime was stopped. Dermatology consultation was sought. Based on clinical presentation, the patient was diagnosed to have SJS/TEN overlap syndrome. He was treated with intravenous linezolid 600 mg twice daily, topical antibiotics and symptomatic management. The patient recovered, skin lesions subsided and he was discharged from the hospital in a stable condition after 2 weeks of in-hospital stay. The present case documents the rare occurrence of SJS/TEN overlap syndrome as an adverse drug reaction with cefuroxime treatment.